Strategies to Increase Airline Ticket Sales by the End of the Year - Esti Liana (Dinasti International Journal of Education Management And Social Science, 2024)
To provide an in-depth understanding of the various results of articles related to papers with variable sales improvement strategies. The method used in this paper is qualitative by reviewing scientific articles related to describing the findings related to this paper, after that the results in this paper are in the form of perceptions in discussions and conclusions. The articles used from the last ten years come from existing international journals. Technology can help and provide speed and become a symbol for the world of aviation around the world, in addition to diverse and attractive services provide a guarantee and variety of choices for passengers.